Digitalization on Micro, Small, and Medium Enterprises (MSMEs) : A Systematic Literature Review - Panduwinata, Lifa Farida; Subroto, Waspodo Tjipto; Sakti, Norida Canda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research explores the impact of digitalization on Micro, Small, and Medium Enterprises (MSMEs) using a systematic literature review (SLR) approach based on the PRISMA method. The data collection process began with the identification of relevant scientific articles using the keywords